文章目录
- 谓词等值式与蕴涵式
- 定理3.1 量词与否定联结词之间有如下关系:
谓词等值式与蕴涵式
序号 | 公式 |
---|---|
E 23 E_{23} E23 | ∃ x ( A ( x ) ∨ B ( x ) ) ⇔ ∃ x A ( x ) ∨ ∃ x B ( x ) \exist x(A(x) \lor B(x)) \Leftrightarrow \exist x A(x) \lor \exist x B(x) ∃x(A(x)∨B(x))⇔∃xA(x)∨∃xB(x) |
E 24 E_{24} E24 | ∀ x ( A ( x ) ∧ B ( x ) ) ⇔ ∀ x A ( x ) ∧ ∀ x B ( x ) \forall x (A(x) \land B(x)) \Leftrightarrow \forall x A(x) \land \forall x B(x) ∀x(A(x)∧B(x))⇔∀xA(x)∧∀xB(x) |
E 25 E_{25} E25 | ¬ ∃ x A ( x ) ⇔ ∀ x ¬ A ( x ) \lnot \exist x A(x) \Leftrightarrow \forall x \lnot A(x) |